2018
DOI: 10.1371/journal.pone.0208835
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibromin haploinsufficiency results in altered spermatogenesis in a mouse model of neurofibromatosis type 1

Abstract: The fertility of men with neurofibromatosis 1 (NF1) is reduced. Despite this observation, gonadal function has not been examined in patients with NF1. In order to assess the role of reduced neurofibromin in the testes, we examined testicular morphology and function in an Nf1+/- mouse model. We found that although Nf1+/- male mice are able to reproduce, they have significantly fewer pups per litter than Nf1+/+ control males. Reduced fertility in Nf1+/- male mice is associated with disorganization of the seminif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Haploinsufficiency-a mechanism by which a loss-of-function mutation leaves only one functional copy of a gene and so leads to insufficient gene product (Deutschbauer et al, 2005)-is a major cause for developmental disorders (Kurotaki et al, 2002;Meechan et al, 2007), including male infertility (Chohan et al, 2018;Zhang et al, 2004). Haploinsufficiency phenotypes typically involve key genes that encode transcription factors and/or function in developmental processes (Dang et al, 2008;Deutschbauer et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Haploinsufficiency-a mechanism by which a loss-of-function mutation leaves only one functional copy of a gene and so leads to insufficient gene product (Deutschbauer et al, 2005)-is a major cause for developmental disorders (Kurotaki et al, 2002;Meechan et al, 2007), including male infertility (Chohan et al, 2018;Zhang et al, 2004). Haploinsufficiency phenotypes typically involve key genes that encode transcription factors and/or function in developmental processes (Dang et al, 2008;Deutschbauer et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The set of head morphology defects observed in Ago2 cKO sperm parallels the defects expected following depletion of several of the proteins downregulated in Ago2 cKO post-meiotic germ cells, including HMGB2, YBX2, and PTBP2 (Catena et al, 2006;Hannigan et al, 2018;Lorès et al, 2018;Snyder et al, 2015). Further, at least two of the transcription factors with binding motifs enriched among the set of dual AGO2 ChIP and CLIP targets (NF1 and STAT4; Figure 5J) are known to regulate sperm head formation (Chohan et al, 2018;Herrada and Wolgemuth, 1997). Phenotype enrichment analysis (Weng and Liao, 2017) confirmed that downregulated DEPs were statistically significantly (adjusted P-value ≤ 0.05) enriched for abnormal male germ cell morphology and other reproductive phenotypes including male infertility and arrest of spermatogenesis.…”
Section: Loss Of Ago2 Causes Sperm Head Defects and Impaired Expression Of Proteins Required For Sperm Morphogenesismentioning
confidence: 69%
“…Further, at least two of the transcription factors with binding motifs enriched among the set of dual AGO2 ChIP and eCLIP targets (NF1 and STAT4) ( Fig. 3 K) are known to regulate sperm head formation ( Herrada and Wolgemuth 1997 ; Chohan et al 2018 ). Phenotype enrichment analysis ( Weng and Liao 2017 ) confirmed that down-regulated DEPs were statistically significantly (adjusted P -value ≤ 0.05) enriched for abnormal male germ cell morphology and male infertility.…”
Section: Resultsmentioning
confidence: 99%